부동산 중개보수 산정 시월·전세 전환 배율의 적용에 관한 연구 - 서영천(Young Cheon Seo) (대한부동산학회지, 2024)
최근, 전세 사기 피해의 증가와 전세보증금반환보증보험 가입 시 적용하는 주택공시 가격의 기준을 126%로 낮추게 되면서 임대인과 임차인이 전세보다 월세를 선호하고, 전세자금 대출이자율의 상승으로 인해 주택 임대차 거래에서 월세의 비중은 늘어나고 전세 비중은 감소하고 있다. 부동산 중개보수를 산정하는데 있어 월 차임을 거래금액으로 환산하는데 지금까지는 월차임 × 100의 전환 배율을 일률적으로 적용하였으나, 본 연구에서는 금리가 높아지고 월세 거래가 많아지고 있는 현재 상황에서는 월·전세 전환 배율을 금리변동 등과 연동할 수 있도록 하는 산출식을 도출하였다. 이는, 기준금리와 연동하여 보증금을 월 차임으로 전환하는 기존의 「주택임대차보호법 시행령」의 산출식을 변환한 뒤 사회 경제적 상황을 고려해 도출한 것으로, 10개월분의 월 차임액 합계를 기준금리 + 2%로 나누도록 산출하였고, 이에 따라 계산한 거래대금이 5천만 원 미만인 경우 7개월분의 월 차임액 합계를 기준금리 + 2%로 나누도록 산출하였다. 이를 통해, 향후 금리의 변화와 주택 임대차 시장에서의 전월세 변화에 따른 중개보수를 산정하는데 있어, 합리적인 거래금액을 산출해 낼 수 있다. Recently, landlords prefer monthly rent to jeonse and the increase in jeonse loan interest rates have increased the proportion of jeonse in housing lease transactions and decreased the proportion of jeonse due to the increase in damage from jeonse fraud and the standard of housing price applied when purchasing jeonse deposit return guarantee insurance to 126%. In calculating real estate brokerage fees, monthly rent has been uniformly applied until now, but in the current situation where monthly rent transactions are increasing, a calculation formula has been derived that allows the monthly rent conversion rate to be linked to interest rate fluctuations. This was derived by converting the calculation formula of the existing 「Enforcement Decree of the Housing Lease Protection Act」, which converts the deposit to monthly rent in conjunction with the base rate, and was calculated to divide the total monthly rent for 10 months by the base rate + 2%, and if the transaction value calculated was less than 50 million won, the total monthly rent for 7 months was calculated to be divided by the base rate + 2%. Through this, it is possible to calculate a reasonable transaction amount in calculating the brokerage fee according to changes in interest rates in the future and changes in jeonse and monthly rent in the housing rental market. KCI Citation Count: 0